Proceedings of International Symposium and Exhibition on Formation Damage Control 2002
DOI: 10.2523/73706-ms
|View full text |Cite
|
Sign up to set email alerts
|

Lessons Learned from Acid Pickle Treatments of Deep/Sour Gas Wells

Abstract: Pickle treatments are commonly conducted to remove various contaminants from the wellbore prior to performing chemical treatments in various wells. Introduction of these contaminants into the formation during the treatment can cause loss of well performance, especially in tight formations. These treatments should be designed to remove various contaminants from well tubulars in an efficient and cost effective way.A pickle treatment was designed to clean well tubulars in several wells prior to performing acid fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2002
2002
2006
2006

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 13 publications
0
13
0
Order By: Relevance
“…Details of the pickle treatment itself are described by Nasr-El-Din et al 31 Details of the acid stimulation treatments are reported separately by Nasr-El-Din et al 32 Pickle treatment results from Well C show that the concentration of formic acid in the flowback samples was more than 85% of the concentration in the injected acid (Fig. 7).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Details of the pickle treatment itself are described by Nasr-El-Din et al 31 Details of the acid stimulation treatments are reported separately by Nasr-El-Din et al 32 Pickle treatment results from Well C show that the concentration of formic acid in the flowback samples was more than 85% of the concentration in the injected acid (Fig. 7).…”
Section: Resultsmentioning
confidence: 99%
“…The samples were collected at short time intervals that varied from 0.5 to 5 minutes. Details of the tubing pickle treatments were reported by Nasr-El-Din et al, 31 while the acid stimulation treatment details were reported by Nasr El-Din et al 32 Each sample from these treatments was mixed thoroughly, then accurately diluted with deionized water before determining formic and acetic acid concentrations.…”
Section: Methodsmentioning
confidence: 99%
“…The main objective of pickling super Cr-13 tubulars is to remove pipe dope and other greasy material from the wellbore, before the fracturing treatment. The pickling procedure was similar to that used in low-carbon steel tubulars, 27 however, in the case of super Cr-13, there was no acid used.…”
Section: Field Treatmentsmentioning
confidence: 99%
“…Acid additives included a corrosion inhibitor and a water-wetting agent. More details on the acid formulation were given by Nasr-El-Din et al 2 It is important to note that the gases produced contained hydrogen sulfide. Therefore, a hydrogen sulfide scavenger was added to the acid.…”
Section: Field Applicationmentioning
confidence: 99%